Second plural r-endings in older Danish and Norwegian - D. Vrieland, Seán (Danske Studier, 2019)
The unique second plural imperative ending -er (-ær) in older Danish has been previously explained by Krogh (1995) as enclisis of the plural pronoun *īʀ and of common origin to the Old Norwegian second plural ending -ir, used in all moods. The present article explains the latter as the result of proportional analogy with the dual pronoun (þ)ið < (þ)it whereas the enclisis hypothesis is still the best explanation for the former. Synchronically, the Danish ending functions to differentiate the plural from the singular in the imperative mood.